Case series of massive direct oral anticoagulant ingestion—Treatment and pharmacokinetics data. (12th January 2022) - Delrue, Maxime; Chevillard, Lucie; Stépanian, Alain; Dragoni, Alessandra; Camoin‐Jau, Laurence; Voicu, Sébastien; Malissin, Isabelle; Deye, Nicolas; Gainnier, Marc; Siguret, Virginie; Mégarbane, Bruno
Abstract: Background: Direct oral anticoagulants (DOAC) are widely used due to favourable benefit/risk ratio. However, consequences of massive ingestion have been poorly investigated. Objectives: We aimed to report outcome and pharmacokinetic parameters in patients who massively ingested DOACs. Methods: We conducted a 5‐year cohort study including consecutive massive DOAC ingestion patients admitted to two critical care departments. Patients were managed in accordance with standards of care. We collected the main history, clinical, laboratory, management and outcome data. The time‐course of plasma DOAC concentrations measured using specific assays was modelled. Results: Twelve patients (3F/9M; age, 55 years [41–63], median [25th–75th percentiles]) were included. Ingestions involved rivaroxaban ( n  = 7), apixaban ( n  = 3) and dabigatran ( n  = 2), with presumed doses of 9.4‐fold [5.0–22.0] the full daily dose. Six patients received activated charcoal but no antidote nor blood‐derived product. No bleeding was observed. One patient died due to refractory cardiogenic shock related to bisoprolol co‐intoxication. Highest observed peak plasma concentrations were 1720 ng/ml (rivaroxaban), 750 ng/ml (apixaban) and 644 ng/ml (dabigatran). Times to reach DOAC concentration below 50 ng/ml were ~20–45 h (rivaroxaban), ~125 h (apixaban) and ~30–50 h (dabigatran). Elimination half‐lives were 2.5–25.5 h (rivaroxaban), 22.0 and 36.5 h (apixaban), and 5.8 and 15.5 h (dabigatran), with substantial interindividual variability and prolongation in case of cardiovascular failure related to co‐intoxicants. Charcoal administration, even if delayed, may have contributed to limit toxicity, possibly by reducing absorption and/or enteroenteric recycling. Conclusion: No bleeding was observed in this series of massive DOAC ingestions despite elevated plasma concentrations. No patient required specific haemostatic agents. Charcoal administration should be considered to limit toxicity.